Acculturative Experiences Among Indonesian Graduate Students in Dutch Higher Education - Mukminin, Amirul (Journal of International Students, 2019)
The intent of this enquiry was to describe the results from research on the lived experiences of Indonesian international graduate students at two Dutch public research universities in the northern part of the Netherlands. The students came from diverse backgrounds and experiences in search of quality education for their future career development. The data collection was conducted from 24 Indonesian students on their experiences from their earliest term throughout their education in the Netherlands. Data were gathered through a demographic profile survey and audio recorded in exhaustive interviews. An analysis of the data revealed common issues—unanticipated educational stressors, unimagined social stressors, language issues, and loneliness/isolation. The participants also described potential strategies for coping with these stressors. The common themes symbolize everyday experiences that Indonesian master’s students faced throughout their acculturative process from the earliest term and over time. Implications, future research, and limitations are discussed.